Adaptation of Master of Islamic Education Students at UIN Raden Fatah: A Case Study of Students with Non-Linear Academic Backgrounds - Kurnia Sari, Ana; Idi, Abdullah; Suryana, Ermis (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
Adaptation is meeting a person's internal and external needs by involving mental and behavioral responses that encourage environmental adaptation. Students often face challenges in adjusting socially and academically. This research focuses on the social and academic adjustment of Master of Islamic Religious Education students at Raden Fatah State Islamic University, Palembang. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, interviews, and documentation and validated through extended researcher presence, triangulation, and peer discussion. This research concludes that students of the Master of Islamic Religious Education at Raden Fatah State Islamic University, Palembang, show good adaptability in the campus environment. They prioritize social recognition, participation, altruism, and effective communication. The results show good academic achievement, supported by commitment, planning, and consistency in academic tasks. Effective strategies such as time management and understanding the material help them overcome academic challenges. Participation in extracurricular activities also makes a positive contribution to academic development. Their awareness, dedication, and commitment to achievement reflect their readiness to face continuous learning challenges. This research provides important insights for developing supporting strategies to improve student well-being and academic success.